2018
DOI: 10.1021/acs.orglett.8b02424
|View full text |Cite
|
Sign up to set email alerts
|

A Ring Contraction of 2,3-Di-O-Silylated Thiopyranosides To Give Thiofuranosides under Mildly Acidic Conditions

Abstract: A pyranose ring contraction of ethyl 1-thio-β-d-galactopyranosides has been discovered that proceeds with retention of aglycon under mildly acidic conditions (aq TFA in CH2Cl2). Key factors for success of this rearrangement are the presence of bulky silyl (TIPS or TBDPS) substituents at both O-2 and O-3 and a free hydroxy group at C-4 (derivatives with acid-labile protective groups at O-4 will also engage in this reaction). The rearrangement cleanly proceeds for 2,3-di-O-TIPS derivatives with two hydroxy grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
(45 reference statements)
1
25
0
Order By: Relevance
“…1,75 We have recently reported that the cleavage of 4,6-O-benzylidene group in derivatives of b-congured ethyl 1-thio-b-D-galactopyranoside with silyl (TIPS or TBDPS) groups at O-2 and O-3 with 80% aq AcOH (80 C, 1 h) gave the expected 4,6-diols in 68-75% yields, while treatment with aq TFA in CH 2 Cl 2 led to pyranose ring contraction. 76 To study the effect of anomeric conguration on the result of treatment of benzylidene acetals with acids, we synthesised ethyl 4,6-O-benzylidene-1-thio-a-Dgalactopyranoside (1) and the corresponding 2,3-O-TIPS 2 3 with TBDPS groups at O-2 and O-3 under identical conditions (according to method B) ( Fig. 1) at the same concentration (c ¼ 48 mmol L À1 ) gave diol 8 and 6-O-acetylated product 9 in 39 and 35% yields, respectively (Fig.…”
Section: Cleavage Of 46-o-benzylidene Group By Aqueous Acoh With Conmentioning
confidence: 99%
“…1,75 We have recently reported that the cleavage of 4,6-O-benzylidene group in derivatives of b-congured ethyl 1-thio-b-D-galactopyranoside with silyl (TIPS or TBDPS) groups at O-2 and O-3 with 80% aq AcOH (80 C, 1 h) gave the expected 4,6-diols in 68-75% yields, while treatment with aq TFA in CH 2 Cl 2 led to pyranose ring contraction. 76 To study the effect of anomeric conguration on the result of treatment of benzylidene acetals with acids, we synthesised ethyl 4,6-O-benzylidene-1-thio-a-Dgalactopyranoside (1) and the corresponding 2,3-O-TIPS 2 3 with TBDPS groups at O-2 and O-3 under identical conditions (according to method B) ( Fig. 1) at the same concentration (c ¼ 48 mmol L À1 ) gave diol 8 and 6-O-acetylated product 9 in 39 and 35% yields, respectively (Fig.…”
Section: Cleavage Of 46-o-benzylidene Group By Aqueous Acoh With Conmentioning
confidence: 99%
“…Changes in the conformations of monosaccharides expectedly accompany their modification with different functional groups. Thus, spatial repulsion of silyl groups results in inversion or distortion of the pyranoside ring [12], which strongly modifies the chemical behaviour of the pyranoside substrate by influencing the spatial environment of the reaction center and changing stereoelectronic effects [35]. A rather complex case is observed for sulfate groups; in addition to van der Waals interactions their negative charges contribute to the electrostatic forces.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the corresponding protected furanose isomer 17b was investigated starting from the pyranose derivatives. Many excellent pyranose-to-furanose isomerisation protocols have been reported, [45][46][47][48][49][50] which unfortunately are not all applicable starting from 16a due to the presence of the vicinal fluorine motif at C2 and C3. We first envisaged to obtain the furanose 17b following an acetylation/isomerisation precedent with 2-deoxy-2fluorogalactose 21 from Liu and co-workers (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%